PSYCHOLOGICAL FEATURES OF THE EFFECTIVENESS OF THE ACTIVITY OF THE HEAD OF A MEDICAL INSTITUTION IN CRISIS CONDITIONS (Psychology Travelogs, 2025)
The article is devoted to the consideration of theoretical and practical aspects related to the activities of the head of a medical institution, the socio-psychological climate in the team and interpersonal relations in it. The paper presents the results of an empirical study conducted during 2021-2023. 158 medical workers and heads of various medical institutions in Odessa participated in the empirical study. The study used author's questionnaires to analyze the socio-psychological characteristics of management of medical institutions in crisis conditions, as well as to study the personal qualities of an effective head of a medical institution. The method of expert assessments and standardized psychodiagnostics methods were also used to study psycho-emotional states, psychological climate in the work team, leadership styles and interpersonal relationships.Based on empirical research, the relationship between the styles of interpersonal interaction between team members and managers, intragroup relations and the characteristics of the psycho-emotional sphere of managers with the effectiveness of their activities in the conditions of the COVID-19 pandemic has been established. Psychological features of managing a medical institution during a pandemic have been identified, including excessive emotional tension and stress, a high level of professional and moral and ethical responsibility, lack of managerial experience and/or competence for working in crisis conditions, psychophysical overload, lack of full rest, work in extreme mode, etc. Psychological factors and patterns of the effectiveness of the head of a medical institution in crisis conditions have been identified. A mini-profile of the personality of an effective head of a medical institution operating in crisis conditions has been developed.
Keywords: psychological characteristics; manager; leadership style; manager ethics; performance effectiveness; medical institutions; crisis conditions